Análise numérica e experimental do efeito de pino em lajes maciças de concreto armado - Oliveira Filho, Márcio Alves de (2019)
In this work, the behavior of slabs subjected to shear force focusing on the dowel action was studied. It is known that the dowel action is one of the mechanisms resistant to shear strength. In this sense, numerical modeling was performed using ANSYS® software, varying the parameters that according to the literature influence the shearing strength, in this way 27 models were performed varying: height, rate of reinforcement, compressive strength of concrete (fck) and parameter αA. This parameter which is a coefficient which allows consider or not the transfer of shear in the crack, because the dowel action is the shear strength that longitudinal reinforcement possesses through a crack. After the modeling by performing a statistical analysis ANOVA and by means of ratio f, it was defined which parameter was influent in the shear strength of the slab. To complement the numerical data, the experimental program was started, in which the assembly of the formwork, reinforcement, steel tensile test, Young modulus test, concrete tensile and compression test were performed. The research aims to evaluate which are the parameters that interfere in the shear force resistance and the dowel action, compare numerical, experimental and normative data to better understand the equations and later define which part of the shear force was related to the phenomenon. There is a test proposal for analysis of the dowel action and the isolated shear strength mechanisms. The results of the shear test slabs and the dowel action test samples were promising for normative parameters (equations and parameter K), rupture modes, displacement analysis, concrete and steel deformations, cracking pattern, among other analyzes.